DISTRIBUSI DAN PROFIL VEGETASI LAURACEAE DI HUTAN WORNOJIWO CIBODAS - Junaedi, Decky Indrawan; Gumilang, Anggun Ratna (Center for Plant Conservation Bogor Botanic Garden, Indonesian Institute of Sciences, 2009)
Research on distribution and vegetation profile of Lauraceae family was conducted in Wornojiwo remnant forest that located inside Cibodas Botanic Garden. Total of 174 plots (10 m to 10 m each) were set and Lauraceae trees with more than 10 cm dbh were recorded. Vegetation analysis for Lauraceae was conducted. Based on the observation, 7 trees of 6 species of Lauraceae was recorded in the forest, i.e. Cryptocarya ferrea, Cinnamomum cassia, Litsea mappacea, Persea rimosa, Persea excelsa and Phoebe grandis. Most of the canopy trees were located in the top layer (layer 4 and 3).